Luteolin Prevents Cardiometabolic Alterations and Vascular Dysfunction in Mice With HFD-Induced Obesity - Gentile, Daniela; Fornai, Matteo; Pellegrini, Carolina; Colucci, Rocchina; Benvenuti, Laura; Duranti, Emiliano; Masi, Stefano; Carpi, Sara; Nieri, Paola; Nericcio, Anna; Garelli, Francesca; Virdis, Agostino; et al. (Frontiers in Pharmacology, 2018)
Purpose Luteolin exerts beneficial effects against obesity-associated comorbidities, although its influence on vascular dysfunction remains undetermined. We examined the effects of luteolin on endothelial dysfunction in a mouse model of diet-induced obesity. Methods Standard diet (SD) or high-fat diet (HFD)-fed mice were treated daily with luteolin intragastrically. After 8 weeks, body and epididymal fat weight, as well as blood cholesterol, glucose and triglycerides were evaluated. Endothelium-dependent relaxations of resistance mesenteric vessels was assessed by a concentration-response curve to acetylcholine, repeated upon L-NAME or ascorbic acid infusion to investigate the influence of nitric oxide (NO) availability and reactive oxygen species (ROS) on endothelial function, respectively. Intravascular ROS production and TNF levels were measured by dihydroethidium dye and ELISA, respectively. Endothelial NO synthase (eNOS) and superoxide dismutase 1 (SOD1), as well as microRNA-214-3p expression were examined by Western blot and RT-PCR assays, respectively. Results HFD animals displayed elevated body weight, epididymal fat weight and metabolic indexes. Endothelium-dependent relaxation was resistant to L-NAME and enhanced by ascorbic acid, which restored also the inhibitory effect of L-NAME, suggesting a ROS-dependent reduction of NO availability in HFD vessels. Moreover, media-lumen ratio, intravascular superoxide anion and TNF levels were increased, while vascular eNOS, SOD1 and microRNA-214-3p expression were decreased. In HFD mice, luteolin counteracted the increase in body and epididymal fat weight, and metabolic alterations. Luteolin restored vascular endothelial NO availability, normalized the media-lumen ratio, decreased ROS and TNF levels, and normalized eNOS, SOD1 and microRNA-214-3p expression. Conclusion Luteolin prevents systemic metabolic alterations and vascular dysfunction associated with obesity, likely through antioxidant and anti-inflammatory mechanisms.